2019
DOI: 10.15761/tim.1000210
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides, novel solution for the treatment of precancerous disease acne - A review

Abstract: Acne is one of the most common epithelial diseases affecting approximately 80% of the world's population between the ages of 16 and 35. It is caused by multiple factors such as genetic predisposition and hormonal alteration including growth factor IGF-I, among others.Acne being related to IGF-I expression, is involved in possible apparition of malignant diseases. The pathology of acne is limited to the pilosebaceous unit. The evolution is governed by the increase in colonization of the bacteria Propionibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…SARS-CoV-2 is the etiological agent responsible for the pandemic COVID-19 outbreak and the main protease (Mpro) of SARS-CoV-2 is a key enzyme that plays an important role in helping in viral replication and transcription. Structure-based design of antiviral drug candidates targeting the SARS-CoV-2 main protease [91].…”
Section: Future Suggestions In Aakashmoni Researchmentioning
confidence: 99%
“…SARS-CoV-2 is the etiological agent responsible for the pandemic COVID-19 outbreak and the main protease (Mpro) of SARS-CoV-2 is a key enzyme that plays an important role in helping in viral replication and transcription. Structure-based design of antiviral drug candidates targeting the SARS-CoV-2 main protease [91].…”
Section: Future Suggestions In Aakashmoni Researchmentioning
confidence: 99%
“…[9,15,19,20,[25][26][27][28][29][30][31]34,108] It is reported that as an internal treatment, the innate response of the patient's immune system to the presence, and current antimicrobial peptides that could be used as potential therapeutic agents against microorganisms located in the skin and related to acne disease. [109] The WHO, Africa welcomes innovations around the world including repurposing drugs, traditional medicines, and developing new therapies in the search for potential treatments for COVID-19 and the people of Africa deserve to use medicines tested to the same standards as people in the rest of the world and the therapies are derived from traditional practice and natural, establishing their efficacy and safety through rigorous clinical trials is critical [110] and COVID-19 vaccine develops using new, fast-growing native "Plant-based Technology." [34,48,49,69,70,[111][112][113]…”
Section: Traditional Medicinementioning
confidence: 99%
“…The drugs obtained from wild plants and animals are not only used as traditional medicines but also as raw materials in the formulation of modern allopathic and herbal preparations [46,80]. It is reported that as an internal treatment, the innate response of the patient's immune system to the presence of an invading microorganism has been studied, highlighting anti-microbial peptides as the host's own defense molecules which shows a compilation of the most relevant and current antimicrobial peptides that could be used as potential therapeutic agents against microorganisms located in the skin and related to acne disease [81]. The World Health Organization, Africa welcomes innovations around the world including repurposing drugs, traditional medicines, and developing new therapies in the search for potential treatments for COVID-19 and the people of Africa deserve to use medicines tested to the same standards as people in the rest of the world and the therapies are derived from traditional practice and natural, establishing their efficacy and safety through rigorous clinical trials is critical [40].…”
Section: On Traditional Medicinementioning
confidence: 99%